Stress intensity factors of edge cracks in dissimilar joint plates - Nik Ismail, Nik Ainun (2014)
Nowadays, there are many applications in which need the combination or different materials. The development of this is caused by the mechanical wear problem, a high temperature situation or other conditions in which different properties are required from different parts of the same applications. This problem brings about the need for joining dissimilar materials. However the combination process between two dissimilar materials can caused mechanical mismatch and may lead to catastrophic failure or crack. Hence, this study will focused on the stress intensity factor on edge crack between dissimilar joint plates. The study focused on the investigation of edge crack behavior of dissimilar joint plates and to find out stress intensity factor (SIF) of dissimilar joint plates under different conditions by using finite element software. In this research, the investigation simulation are conducted by using finite element analysis software, ANSYS. A program that consist a coding of joining dissimilar material with centre and offset edge crack have been developed using ANSYS software. Data of stress intensity factor, K produced by ANSYS software then transform to dimensionless stress intensity factor, F. Relationship between mechanical mismatch, α, ratio of stress, β, relative crack depth, a/w and relative offset distance, b/h to the dimensionless SIF, F are analyze and discussed.